Identifying 21st Century STEM Competencies Using Workplace Data - Jang, Hyewon (Journal of science education and technology, 2016)
Gaps between science, technology, engineering, and mathematics (STEM) education and required workplace skills have been identified in industry, academia, and government. Educators acknowledge the need to reform STEM education to better prepare students for their future careers. We pursue this growing interest in the skills needed for STEM disciplines and ask whether frameworks for 21st century skills and engineering education cover all of important STEM competencies. In this study, we identify important STEM competencies and evaluate the relevance of current frameworks applied in education using the standardized job-specific database operated and maintained by the US Department of Labor. Our analysis of the importance of 109 skills, types of knowledge and work activities, revealed 18 skills, seven categories of knowledge, and 27 work activities important for STEM workers. We investigate the perspectives of STEM and non-STEM job incumbents, comparing the importance of each skill, knowledge, and work activity for the two groups. We aimed to condense dimensions of the 52 key areas by categorizing them according to the Katz and Kahn (1978) framework and testing for inter-rater reliability. Our findings show frameworks for 21st century skills and engineering education do not encompass all important STEM competencies. Implications for STEM education programs are discussed, including how they can bridge gaps between education and important workplace competencies.